Paraneoplastic syndromes secondary to neuroendocrine tumours. - Kaltsas, G; Androulakis, I; de Herder, W; Grossman, AB (2010)
Neuroendocrine tumours may be either benign or malignant tumours, and have the ability to synthesise and secrete biologically active substances characteristic of the cell of origin that can cause distinct clinical syndromes. The term 'paraneoplastic syndromes' (PNSs) is used to denote syndromes secondary to substances secreted from tumours not related to their specific organ or tissue of origin and/or production of autoantibodies against tumour cells; such syndromes are mainly associated with hormonal and neurological symptoms. Appreciation of the presence of such syndromes is important as clinical presentation, if not identified, may delay the diagnosis of the underlying neoplasia. Conversely, early recognition can allow for more rapid diagnosis, particularly as the coexistence of a neoplasm with a clinical or biochemical marker offers an additional determinant of tumour status/progression. PNSs can complicate the patient's clinical course, response to treatment, impact prognosis and even be confused as metastatic spread. Their diagnosis involves a multidisciplinary approach, and detailed endocrinological, neurological, radiological and histological studies are required. Correct diagnosis is essential as the treatment of choice will be different for each disorder, particularly in the case of malignant tumours; it is therefore important to develop appropriate means to correctly identify and localise these tumours. Clinical awareness and the incorporation into clinical practise of (111)In-octreotide scintigraphy, chromogranin A and other evolving biochemical marker measurement techniques have substantially contributed to the identification of patients harbouring such syndromes. Disease-specific medical therapies are mandatory in order to prevent recurrence and/or further tumour growth. Owing to their rarity, central registration of these syndromes is very helpful in order to be able to provide evidence-based diagnostic and therapeutic approaches.